MODELS OF EFFICIENCY EVALUATION DEVELOPMENT PROGRAM OF EMPLOYEES' COMPETENCES (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. Staff competence is a strategic resource of the enterprise. Therefore, personnel management should provide the necessary conditions for their formation and development. An enterprise that operates in accordance with the principle of efficient management should consider the costs and benefits of implementing competency development programs. This means comparing the level of competence of individual employees before and after training. The result of such an audit allows us to identify training programs that are beneficial to employees and effective for the enterprise.This purpose of the article is to systematize the experience of methods of evaluating the effectiveness of training programs for the development of employees' competences with a view to their perception of domestic practice.Results. There are two types of competences: the necessary ones that follow from the prepared job profiles and outline the requirements for those who will perform this work in a certain workplace (position); acquired, which employees are acquired and used on the job. Therefore, the main purpose of competency development at the enterprise is to achieve a better match between the necessary and actual levels of competence. Development involves improving the already acquired competences and mastering completely new ones.Employee competencies are developed in different ways. These are: learning through experience; use of employees as assistants, trainees; preparation in project teams; information and advice received from others (coaching, mentoring, consultations, meetings with experts); conferences, seminars, trainings taking various forms.The diversity of approaches is explained by the fact that the development needs of each enterprise are different. In addition, the methods used must be adapted to the changing environmental conditions.The article discusses the advantages and disadvantages of the most commonly used enterprise competence development models of performance assessment programs, including the Kirkpatrick model and its modified version by J. Phillips, the CIPP model, and R. Brinkerhoff's "case of success.Conclusions. In order to ensure that domestic practice of foreign experience is accepted, research into the methodology of assessing the effectiveness of personnel training should move in the direction of systematic decomposition of foreign models and taking into account the peculiarities of the national economy.
Keywords: competences, learning objectives, curriculum effectiveness, curriculum evaluation, assessment models